Environmental Certifications as a Catalyst for Advancing Circular Supply Chains - SANHAJI , Nada; KHARISS , Mohammed (Revue Internationale des Sciences de Gestion, 2025)
Environmental certifications are crucial in changing supply chains in a global setting where ecological transition and sustainability have emerged as significant issues. They encourage businesses to embrace more environmentally friendly practices and guarantee adherence to stringent environmental requirements. In order to encourage a circular supply chain, this article examines how certifications like ISO 14001., Cradle to Cradle (C2C), LEED (Leadership in Energy and Environmental Design), and European eco-labels can be effective levers. These certifications force businesses to reconsider their production and logistical plans by defining precise environmental standards and including the concepts of resource efficiency, waste minimization, and recyclability. This study emphasizes the critical role that certifications play in promoting sustainable supply chain management through an examination of current research and real-world case studies. It looks at how they affect stakeholder cooperation, consumer trust, and business environmental performance. The essay also addresses the difficulties and restrictions that come with putting these certificates into practice, such as the financial limitations that SMEs have and the difficulty of juggling several certification programs. In the end, this study emphasizes that environmental certifications are strategic facilitators for the shift to a more sustainable and circular economy, not just compliance instruments. The transition to more robust and environmentally friendly supply chains may be accelerated by their broad adoption in conjunction with standardized regulatory frameworks and funding sources.